2011
DOI: 10.1007/s11010-011-1081-1
|View full text |Cite
|
Sign up to set email alerts
|

Time-sequential modulation in expression of growth factors from platelet-rich plasma (PRP) on the chondrocyte cultures

Abstract: Platelets are involved in hemostasis, wound healing, and tumor growth. Autologous blood products are commonly used to facilitate healing in a variety of clinical surgery applications. Recently, it was shown that platelet-rich plasma (PRP) has more specific growth factors that participate in the healing process. This study investigated the expression of PRP growth factors and evaluated their potential role in the cartilage regeneration using primary isolated chondrocytes. PRP obtained from New Zealand White rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
1
46
0
4
Order By: Relevance
“…PRPr can be an economic and valuable source for autologous and highly concentrated growth and differentiation factors (Wu et al 2007;Sawamura et al 2009), whose application in clinical practice (Borzini and Mazzucco, 2005;Smith and Roukis, 2009;Lopez-Vidriero et al 2010;Andia et al 2011) as well as in cartilage tissue engineering (Anitua et al 2005;Gaissmaier et al 2005;Kanno et al 2005;Mishra et al 2009;Wu et al 2011;Park et al 2012) has been widely documented. In particular, in a previous study we have reported the efficacy of PRP releasates obtained by means of an optimized and standardized protocol to maintain chondrocyte-like phenotype in monolayer cultures of human articular chondrocytes (Spreafico et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PRPr can be an economic and valuable source for autologous and highly concentrated growth and differentiation factors (Wu et al 2007;Sawamura et al 2009), whose application in clinical practice (Borzini and Mazzucco, 2005;Smith and Roukis, 2009;Lopez-Vidriero et al 2010;Andia et al 2011) as well as in cartilage tissue engineering (Anitua et al 2005;Gaissmaier et al 2005;Kanno et al 2005;Mishra et al 2009;Wu et al 2011;Park et al 2012) has been widely documented. In particular, in a previous study we have reported the efficacy of PRP releasates obtained by means of an optimized and standardized protocol to maintain chondrocyte-like phenotype in monolayer cultures of human articular chondrocytes (Spreafico et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On gross assessment, the PRP-treated graft borders were less demarcated compared with the control grafts, and there was a significant improvement in scoring of the integration at the cartilage interface on histological assessment. Chondrocyte viability and proliferation are increased in the presence of PRP 50,52,53 . Additionally, chondrocytes cultured with PRP may increase their proteoglycan deposition and type-II collagen content 22,24,53 , potentially increasing the quality and quantity of repair tissue at the chondral interface.…”
Section: Macroscopic and Histological Appearance Of The Osteochondralmentioning
confidence: 99%
“…PRP brings about its effect in osteoarthritis by stimulating cartilage matrix metabolism. [14][15][16][17] Since it is autologous, there is no risk of allergic reactions or disease transmission. There are no side effects.…”
Section: Discussionmentioning
confidence: 99%